Hearths and bones: An experimental study to explore temporality in archaeological contexts based on taphonomical changes in burnt bones. (February 2017) - Pérez, Leopoldo; Sanchis, Alfred; Hernández, Cristo M.; Galván, Bertila; Sala, Robert; Mallol, Carolina
Abstract: Although the occurrence of burned bones in the archeological record has been widely investigated, very few studies have focused on the distinction of temporality in burned bones assemblages, which would be useful in helping to identify human activity areas, as well as distinguishing combustion residues from those resulting from other activities. In this work, we present the results of an experiment designed to characterize direct/indirect thermal alteration of rabbit bones, based on macroscopic and microscopic surface features. These results are then compared with an archeological burned bone assemblage associated with various Middle Paleolithic combustion structures from El Salt Stratigraphic Unit X (Alicante, Spain). In the experimental assemblage, we observed that rabbit bones tossed into a fire were strongly altered, while bones thrown on the cooled ashes and lying on the surface beneath the fire or slightly buried, were not. We observed a strong thermal surface alteration of fresh bone (color changes, high degrees of fragmentation, cracks and structural changes on the cortical surface), while dry bone showed only color changes. Taking this data into account when analyzing the archeological assemblage, we observed surface features corresponding to thermally altered fresh bone and others more like thermally altered dry bone. Crucially, the archaeological specimens are associated with black layers of combustion structures and exhibit signs of trampling. The results suggest that fresh bones were trampled into human occupation surfaces and were subsequently unintentionally or indirectly burned due to their position beneath hearths, along with other dry bones present there. Our study shows that investigating ways to distinguish temporality in burned bones may be a good tool for isolating different depositional events and thus contributing to archeological palimpsest dissection. Highlights: Combustion experiments contribute to understanding formation of bones assemblage. Burned bone assemblages may result from unintentional burning. Isolating depositional events on archaeological burned bone assemblages it is possible. Fresh and dry bones are differentially altered when exposed to fire. Optical microscopy at 70 × is an optimal resolution to identify bone alterations.